Relational Coaching in Sport: Its psychological underpinnings and practical effectiveness - Jowett, S.; Shanmugam, V. (International Handbook of Sport Psychology, 2016)
Introduction: Setting the Scene Why do some coaches deliver results while others don`t quite manage to make their mark? In Europe, an example of extraordinary coaching success is Marcus Weise, field hockey coach - maintained his successful streak over the past 10 years or so. His coaching efforts as well as apparent energy and commitment culminated to Gold in Athens 2004 with the German Women`s Olympic hockey team as well as Gold in Beijing 2008 and Gold in London 2012 with the German Men`s Olympic hockey team. He is the only coach to have won gold with a men`s and a women's team. In an interview, he was asked how he coaches his athletes and among others he said: that coaching is discovering the capacities and capabilities that his players hide and he went on to say that "when you coach you need to find a door that enables you to get access to the player". They are so many examples of exceptionally effective and successful coaches, in individual sports (e.g., Toni Minichiello and Jessica Ennis) and team sports (e.g., Alex Ferguson, Jose Mourinho). What these extraordinary coaches have in common is their desire and capacity to unlock their athletes` hidden potential in order to maximise their chances to achieve success. Coaches who believe that their athletes possess more future potential than they presently demonstrate, are more likely to get the best out of their athletes and hence help them succeed. But how can an athlete`s hidden potential be released? It can be released when coaches and athletes start to form a genuine working relationship, where they trust, respect, believe, commit and work together toward one goal. This interpersonal connection between the coach and each athlete in the team or squad, often referred to as "relational coaching", lies at the heart of effective and successful coaching. Two-Person Relationships at the Heart of Relational Sport Coaching To be a technically good coach is one thing, but what gives the coach the "edge" (i.e., the extra effectiveness) in this unforgiving and relentless competitive sport environment, is the connection developed between the coach and athlete (see Figure 1). It is this connection that makes a difference to technical coaching because it supplies coaches with the key to opening the door to their athlete`s capabilities, capacities, and potential. The best athletes in the world (following success in World, Olympic Championships) often state that their coaches have been instrumental to their success. In contrast, it is rare to hear athletes who have won gold medals and broken records attacking and criticising their coaches. This is neither random nor coincidental. This unique partnership or relationship developed between a coach and an athlete, we call relational coaching. Relational coaching is the ways coaches and athletes connect to bring about performance success and personal satisfaction.